2022
DOI: 10.1021/acsomega.2c04647
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Isopropyl Alcohol Conversion over Acidic Nickel Phosphate-Supported Zeolite Catalysts

Abstract: In this preliminary research, the catalytic activity of isopropyl alcohol conversion to diisopropyl ether through dehydration reaction catalyzed by zeolite-Ni and zeolite-Ni(H2PO4)2 was comparatively described. The natural zeolite was treated with 1% HF and 6 N HCl prior to modifications using the impregnation method. Isopropyl alcohol conversion was examined at a mild temperature of 150 °C for 3.5 h on the reflux system with various catalyst loadings. X-ray diffraction and Fourier transform infrared analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 84 publications
0
4
2
Order By: Relevance
“…The specific surface area of the clay was measured using the Brunauer-Emmett-Teller (BET) method as shown in Figure 2 and the interpretation in Table 1. The specific surface area was found to be 59.26 m 2 /g greater than previous study (Hasanudin et al, 2022). It indicates that the clay has a relatively large surface area, which can affect its water retention properties.…”
Section: Results and Disscussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The specific surface area of the clay was measured using the Brunauer-Emmett-Teller (BET) method as shown in Figure 2 and the interpretation in Table 1. The specific surface area was found to be 59.26 m 2 /g greater than previous study (Hasanudin et al, 2022). It indicates that the clay has a relatively large surface area, which can affect its water retention properties.…”
Section: Results and Disscussioncontrasting
confidence: 56%
“…Based on the results of this study, it can be concluded that the clay from the Pattalassang district exhibits platelet-shaped XRD patterns with a distribution of 75% particles that are between 5 and 25 nm (based on Equation1).The specific surface area of the clay was measured using the Brunauer-Emmett-Teller (BET) method as shown in Figure2and the interpretation in Table1. The specific surface area was found to be 59.26 m 2 /g greater than previous study(Hasanudin et al, 2022). It indicates that the clay has a relatively large surface area, which can affect its water retention properties.…”
contrasting
confidence: 53%
See 1 more Smart Citation
“…The S BET of SiO 2 /Zr was lower S BET compared with the parent SiO 2 owing to the pore blocking of Zr species. 41 Despite the fact that the SiO 2 /Zr-KHF2 prepared by the template method exhibited a decrease in S BET , this method increased the total pore volume ( V p ), suggesting an enhancement in the pore features of the catalyst. Conversely, SiO 2 /Zr-KHF1 prepared using the chelate method significantly decreased the pore volume.…”
Section: Resultsmentioning
confidence: 96%
“…The textural properties of the parent SiO 2 and its modifications are listed in Table . The S BET of SiO 2 /Zr was lower S BET compared with the parent SiO 2 owing to the pore blocking of Zr species . Despite the fact that the SiO 2 /Zr-KHF2 prepared by the template method exhibited a decrease in S BET , this method increased the total pore volume ( V p ), suggesting an enhancement in the pore features of the catalyst.…”
Section: Resultsmentioning
confidence: 96%